The Guidelines on Development of School Based Management for School Under Khon Kaen Primary Educational Service Area Office 1 - Settanant, Napapach; Chanawongse, Amnaj; Laoprasert, Sathian (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to: 1) study the current conditions, desired conditions, and needs for school-based management in schools; and 2) explore development guidelines for school-based management in schools under the Office of Khon Kaen Primary Educational Service Area 1. The sample consisted of 336 participants: 24 school administrators and 312 teachers under the Office of Khon Kaen Primary Educational Service Area 1. The research instruments included a dual-response format questionnaire with a 5-point rating scale, a structured interview form, and tools for assessing appropriateness and feasibility. Data were analyzed using frequency, percentage, mean, standard deviation, and the Modified Priority Needs Index (PNImodified) to prioritize the needs. The findings revealed that: 1) the overall and aspect-specific current conditions of school-based management were at a moderate level, whereas the desired conditions were rated at the highest level. The overall PNImodified score for the developmental needs of school-based management was .42. When ranked by aspect, the highest priority need was accountability and checks and balances, followed by decentralization, system-wide development, participation, and self-management. 2) There were 18 proposed guidelines for developing school-based management. The assessment of appropriateness and feasibility showed that, overall, both were rated at the highest level.